Disruption of Interleukin-1 Signaling Improves the Quality of Wound Healing - Thomay, Alan A. (American Society for Investigative Pathology, 2009)
In this study, we investigated the role of interleukin (IL)-1 signaling in wound healing. IL-1 receptor type I (IL-1R) knockout (KO) mice showed reduced fibrosis in both cutaneous and deep tissue wounds, which was accompanied by a reduction in inflammatory cellular infiltration in cutaneous but not in deep tissue wounds. There were no differences in either total collagenolytic activity or in the expression of selected matrix metalloproteinases or tissue inhibitors of metalloproteinases between the wound fluids from wild-type or IL-1R KO mice. However, wound fluids from IL-1R KO mice contained lower levels of IL-6 compared with wild-type controls. In addition, the infusion of IL-6 into wounds in IL-1R KO mice did not increase fibrosis. Skin wounds in IL-1R KO animals had lower levels of collagen and improved restoration of normal skin architecture compared with skin wounds in wild-type mice. However, neither the tensile strength of incisional skin wounds nor the rate of closure of excisional wounds differed between IL-1R KO and wild-type animals. The reduced fibrotic response in wounds from IL-1R KO mice could be reproduced by the administration of an IL-1R antagonist. These findings suggest that pharmacological interference with IL-1 signaling could have therapeutic value in the prevention of hypertrophic scarring and in the treatment of fibrotic diseases.